Common-pool resources, livelihoods, and resilience: Critical challenges for governance in Cambodia - Ratner, Blake D. (International Food Policy Research Institute, 2011)
Common-pool resource management is a critical element in the interlocked challenges of food security, nutrition, poverty reduction, and environmental sustainability. This paper examines strategic policy choices and governance challenges facing Cambodia‘s forests and fisheries, the most economically important subsectors of agriculture that rely on common-pool resources. It then outlines policy priorities for institutional development to achieve improvements in implementing these goals. The core argument is that (1) policy support for community-based management in forestry and fisheries requires explicit prioritization to protect against threats from other types of private- and public-sector investment; and (2) the success of these initiatives depends on more systemic governance reforms that address issues of stakeholder representation, mechanisms of accountability, and institutional capacity.